The Perils of Navigating Activity-Dependent Alternative Splicing of Neurexins - Liakath-Ali, Kif; Südhof, Thomas C. (Frontiers in Molecular Neuroscience, 2021)
Neurexins are presynaptic adhesion molecules essential for synaptic function that are expressed in thousands of alternatively spliced isoforms. Recent studies suggested that alternative splicing at splice site 4 (SS4) of Nrxn1 is tightly regulated by an activity-dependent mechanism. Given that Nrxn1 alternative splicing at SS4 controls NMDA-receptor-mediated synaptic responses, activity-dependent SS4 alternative splicing would suggest a new synaptic plasticity mechanism. However, conflicting results confound the assessment of neurexin alternative splicing, prompting us to re-evaluate this issue. We find that in cortical cultures, membrane depolarization by elevated extracellular K+ concentrations produced an apparent shift in Nrxn1-SS4 alternative splicing by inducing neuronal but not astroglial cell death, resulting in persistent astroglial Nrxn1-SS4+ expression and decreased neuronal Nrxn1-SS4- expression. In vivo, systemic kainate-induced activation of neurons in the hippocampus produced no changes in Nrxn1-SS4 alternative splicing. Moreover, focal kainate injections into the mouse cerebellum induced small changes in Nrxn1-SS4 alternative splicing that, however, were associated with large decreases in Nrxn1 expression and widespread DNA damage. Our results suggest that although Nrxn1-SS4 alternative splicing may represent a mechanism of activity-dependent synaptic plasticity, common procedures for testing this hypothesis are prone to artifacts, and more sophisticated approaches will be necessary to test this important question.